Comprehensive approach to weaning in difficult-to-wean infantile and juvenile-onset glycogen-storage disease type II patients: a case series - Lingling Xu; Hongjun Ba; Yuxin Pei; Xueqiong Huang; Yujian Liang; Lidan Zhang; Huimin Huang; Cheng Zhang; Wen Tang (BMC, 2019)
Abstract Background Glycogen storage disease type II (GSD II) is caused by acid alpha-glucosidase (GAA) deficiency. Both infantile-onset and juvenile-onset GSD II lead to proximal muscle weakness and respiratory insufficiency and require mechanical ventilation. However, GSD II is also independently associated with delayed weaning from mechanical ventilation. This study aimed to describe a comprehensive approach including sequential invasive-noninvasive mechanical ventilation weaning and enzyme replacement therapy (ERT) in patients with weaning difficulties. Case presentation We studied six difficult-to-wean GSD II (three juvenile-onset, three infantile-onset) patients at the First Affiliated Hospital, Sun Yat-sen University from October 2015 to December 2017. Difficulty in weaning was defined as follows: the need for more than three spontaneous breathing trials or more than 1 week to achieve successful weaning. All patients received comprehensive treatment including sequential invasive-noninvasive mechanical ventilation weaning, ERT and general treatment. Recombinant human acid alpha-glucosidase enzyme therapy (20 mg/kg every 14 days) was used after diagnosis, and Patients 1-6 received ERT for 15.5, 4.5, 2, 2.5, 17, and 2 months, respectively. The therapeutic effect of the comprehensive treatment was observed. The patients' respiratory function and limb muscle strength improved after each ERT session. Patients who successfully completed a spontaneous breathing trial could proceed to extubation, and then start non-invasive ventilation. The patients' age range at initial mechanical ventilation was 3-47 (median 26.5) months, duration of invasive ventilation was 1-36 (median 2.75) months, and duration of noninvasive ventilation was 0-0.6 (median 0.05) month. The patients' nutritional status improved after enhanced nutritional support. Patients 2, 3, and 5 were successfully weaned off the ventilator. Patient 1 underwent tracheal intubation after six weaning failures, and Patients 4 and 6 died after therapy was abandoned by their parents. Discussion and conclusions Male sex, GSD II type, and the presence of malnutrition and neurological impairment may predict poor respiratory outcomes. The above-described comprehensive sequential invasive-noninvasive mechanical ventilation weaning strategy may increase the success rate of weaning from mechanical ventilation.